PCR Detection of DNA Specific for Trichosporon Species in Serum of Patients with Disseminated Trichosporonosis - Nagai, Hiroyuki (American Society for Microbiology, 1999)
Deep-seated trichosporonosis is a lethal opportunistic infection that disseminates rapidly and widely in immunocompromised patients, and early diagnosis is crucial for the treatment of this infection. We developed a novel nested-PCR assay that detects DNA specific for clinically important strains of Trichosporon in serum samples from patients with disseminated trichosporonosis. In this assay, two sets of oligonucleotide primers were derived from the sequence of 26S rRNA genes of Trichosporon asahii. The specific fragment was amplified from T. asahii and T. mucoides, but not from other microorganisms, including some other basidiomycetous fungi (Cryptococcus, Malassezia, Rhodotorula, and Sporobolomyces). Target DNA was detected by the nested PCR with as little as 5 fg of the extracted DNA of T. asahii. In a study using 11 clinical samples, the specific fragment was detected by the nested PCR in 64% (7 of 11) of sera from patients with histologically diagnosed disseminated trichosporonosis, while glucuronoxylomannan antigen was detected in only 54% (6 of 11) of the samples. Our new nested-PCR assay using serum samples can be performed repeatedly throughout the course of the disease. In addition, not only can it be used for early diagnosis of trichosporonosis, but it may also be beneficial for monitoring its progress or response to therapy.